Bi-cytopenia possibly induced by anti-PD-1 antibody for primary malignant melanoma of the esophagus: A case report. Issue 29 (July 2016) - Inadomi, Kyoko; Kumagai, Hozumi; Arita, Shuji; Tsuruta, Nobuhiro; Takayoshi, Kotoe; Mishima, Koji; Ota, Shun-Ichiro; Tanaka, Mamoru; Okumura, Yuta; Sagara, Kosuke; Nio, Kenta; Nakano, Michitaka; et al.
Abstract: Background: Anti-programmed cell death 1 antibody nivolumab is a promising agent for various cancers. Immune-related adverse events are recognized; however, bi-cytopenia with nivolumab has not been reported. Case presentation: A 73-year-old man was diagnosed with advanced primary malignant melanoma of the esophagus with liver, lung, and lymph node metastases. Previous therapies including dacarbazine and radiation of 39 Gy to the esophageal region were performed, but the liver metastases deteriorated. The patient was then administered nivolumab (2 mg/kg, every 3 weeks). After 3 cycles, the esophageal tumor and lymph nodes showed marked reductions in size, the lung metastases disappeared, and the liver metastases shrank partially. The treatment continued with 7 cycles for 4 months. However, severe anemia and thrombocytopenia appeared in the 6th cycle, and intermittent blood transfusions were required. The patient received high-dose intravenous methylprednisolone therapy for bi-cytopenia, but it was ineffective. Seven months after the initiation of nivolumab, the patient died of tumor. Although the mechanisms of bi-cytopenia were unclear, it could have been induced by nivolumab. Conclusion: The present case shows a rare but serious life-threatening bi-cytopenia possibly associated with nivolumab and suggests the importance of awareness of hematological adverse events during nivolumab therapy.